Optimal adaptive spectrum utilization in cellular communications systems - Kazantzakis, M.G.; Demestichas, P.P.; Tzifa, E.C.; Anagnostou, M.E. (IEEE transactions on communications, 1999)
Efficient spectrum utilization in third-generation cellular systems has motivated the study of the traffic adaptive channel allocation problem: given the set of channels, the cell structure and the load to be accommodated in each cell find the optimal allocation of channels to cells, subject to the reuse distance constraints. In this paper, we extend this scheme in order to include time fluctuating traffic loads. The extended problem is formulated and solved by reduction to 0-1 (linear and quadratic) programming.